Decision Making with Analytical Hierachy Process, AHP for Sustainable Car Seat Belt Latch Plate Manufacturing - Kong, Ming Chai; Sia, Chee Kiong (Research Progress in Mechanical and Manufacturing Engineering, 2026)
This study evaluates the sustainable manufacturing of car seat belt latch plates by integrating environmental, social, and economic criteria. The primary objective is to identify the optimal material and manufacturing process to minimize environmental impacts while ensuring safety, performance, and cost-effectiveness. Using SolidWorks tools for sustainability, simulation, and costing, data were compiled on emissions (SO₂, CO₂, PO₄), energy consumption, cost, and safety factors. The Analytic Hierarchy Process (AHP) was employed to systematically evaluate materials like alloy steel, AISI type 316L stainless steel, AISI 304, commercially pure titanium, and Ti-6Al-4V across three manufacturing processes which are 3D printing, machining, and casting. The findings revealed that Ti-6Al-4V is the most suitable material for 3D printing, offering high strength-to-weight ratio and superior safety, despite its higher cost and energy demands. For machining and casting, alloy steel was identified as the best choice due to its cost-effectiveness, energy efficiency, and mechanical robustness, making it ideal for large-scale production. AISI 304 showed moderate suitability in machining and casting, while AISI type 316L stainless steel and commercially pure titanium were less favourable due to higher costs and energy requirements. This study concludes that aligning material and process selection with specific production objectives is crucial for sustainable automotive manufacturing. The AHP methodology ensured consistency in decision-making, balancing environmental, economic, and social factors. The results provide a comprehensive framework for selecting sustainable materials and manufacturing methods, contributing to advancements in automotive safety and sustainability.